PROFIL KEMAMPUAN PENALARAN MATEMATIS SISWA DITINJAU DARI GAYA BELAJAR - Muhamad Ridwan (KALAMATIKA Jurnal Pendidikan Matematika, 2017)
Students learn according to their learning style, and every learning styles are affecting the process of mathematical reasoning and learning outcomes. The combination of how to absorb, manage and process information is the definition of learning styles. To maximize the students' ability to absorb, manage and process information, first identified learning styles of the students are visual, auditory or kinesthetic (V-A-K). This research aims to reveal the profile of mathematical reasoning abilities of students in terms of learning styles visual, audio and kinesthetic on the material function composition and inverse function. This research is a qualitative descriptive approach ethnography and research subject is grade XI of senior high school. The results of the research of profile learning styles (V-A-K) that profile visual students' mathematical reasoning skill, have the ability to manipulate, draw conclusions, giving reasons or evidence is sufficient. While the ability to deliver his argument lacking. Profile auditory students' mathematical reasoning skills, have the ability to manipulate, giving reason or evidence, and provide argument or the validity of the answer is both. While the ability gets conclusion to enough. Profile kinesthetic students' mathematical reasoning skills have the ability to manipulate and give reasons or evidence is sufficient. The ability to draw conclusions while the less, as well as the ability to provide an answer or the validity of the argument, he answered with a unique and clear